Serviços de saúde, a assimetria da informação e a intervenção do governo: os exemplos americano e brasileiro - Nicolini, Miquelina da Fonseca (2014)
The current essay shows how health service market is afected by assimetric information, that results in government intervention. To understand that, an analisis of how this market works has been done, taking in account assimetric information, specially the one brought by adverse selection, shown in Akerlof’s and Rothschild and Stiglitz’s models. Then, specificities of health market were discussed and the intervention of government, justified. At this point, the income distribution that comes from the government intervention is also approached. Finally, as an example, Brazil’s and United States’ models are shown and analised. As a conclusion, the implication of each one of these models, as well as sugestions for another studies in this area.